2007
DOI: 10.1007/s00425-007-0554-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of glycerol-3-phosphate acyltransferase gene improves chilling tolerance in tomato

Abstract: A tomato (Lycopersicon esculentum Mill.) glycerol-3-phosphate acyltransferase gene (LeGPAT) was isolated. The deduced amino acid sequence revealed that LeGPAT contained four acyltransferase domains, showing high identities with GPAT in other plant species. A GFP fusion protein of LeGPAT was targeted to chloroplast in cowpea mesophyll protoplast. RNA gel blot showed that the mRNA accumulation of LeGPAT in the wild type (WT) was induced by chilling temperature. Higher expression levels were observed when tomato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 42 publications
6
50
0
4
Order By: Relevance
“…Moreover, differences in the degree of unsaturation of 16 carbon atoms molecules were detected between the two positions of the PG molecule. A similar finding was reported previously in tomato (Sui et al, 2007), where 16:0 desaturation occurs asymmetrically between positions sn-1 and -2, enriching the sn-1 position in saturated fatty acids and the sn-2 in delta 3-trans-hexadecenoyl (16:1(3t)).…”
Section: Lipid Analysis Of Sunflower Leavessupporting
confidence: 89%
“…Moreover, differences in the degree of unsaturation of 16 carbon atoms molecules were detected between the two positions of the PG molecule. A similar finding was reported previously in tomato (Sui et al, 2007), where 16:0 desaturation occurs asymmetrically between positions sn-1 and -2, enriching the sn-1 position in saturated fatty acids and the sn-2 in delta 3-trans-hexadecenoyl (16:1(3t)).…”
Section: Lipid Analysis Of Sunflower Leavessupporting
confidence: 89%
“…Zhang et al (2005) reported that modulated fatty acid desaturation via over expression of two distinct ω-3 desaturases differentially alters tolerance to various abiotic stresses in transgenic tobacco cells and whole plants. The different substrate selectivity of GPAT enzyme can also affect the cold resistance of plants (Sui et al, 2007). Introduction of the GPAT gene into rice increased the unsaturated fatty acid levels and led to cold resistance (Ariizumi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggested that the changes in the content of unsaturated fatty acids can improve plant tolerance to environmental stresses such as cold, heat and drought (Dakhma et al, 1995;Liu et al, 2008;Matos et al, 2002;Sui et al, 2007). Under chilling stress, lipids in cell membranes change from a lipid-crystalline condition to a solid state at a critical temperature that is determined by the ratio of saturated to unsaturated fatty acids (Quinn, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, tolerance at 1°C for 11 d was conferred using a gene encoding a nonspecific cyanobacterial desaturase, and the resultant transgenic tobacco plants showed a reduction in saturated fatty acid content in membrane lipids (Ishizaki-Nishizawa et al, 1996). The overexpression of glycerol-3-phosphate acyltransferase altered the unsaturation of fatty acids and conferred chilling tolerance in transgenic plants (Ariizumi et al, 2002;Sakamoto et al, 2003;Sui et al, 2007). Hence, modifications in lipid composition that stabilize cell membranes and prevent cellular leakage lead to cold tolerance.…”
Section: Discussionmentioning
confidence: 99%